2021
DOI: 10.3389/fmed.2021.598810
|View full text |Cite
|
Sign up to set email alerts
|

ICD-10-Coding of Medically Unexplained Physical Symptoms and Somatoform Disorders—A Survey With German GPs

Abstract: Background: General practitioners (GPs) are reluctant to use codes that correspond to somatization syndromes.Aim: To quantify GPs' views on coding of medically unexplained physical symptoms (MUPS), somatoform disorders, and associated factors.Design and Setting: Survey with German GPs.Methods: We developed six survey items [response options “does not apply at all (1)”—“does fully apply (6)”], invited a random sample of 12.004 GPs to participate in the self-administered cross-sectional survey and analysed data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…One of the most common mental disorders is somatoform disorders, with estimated prevalence rates of 5-6% in the general population [5]. A meta-analysis study showed that the prevalence rate of patients with at least one somatoform disorder according to DSM or ICD diagnosis criteria in primary healthcare facilities was 26.2%, and the prevalence rate within one year was 18.9% [6]. The highest proportion of patient diagnoses was somatoform disorder, unspecified (F45.9) at 37%, while the least diagnosed patient condition was undifferentiated somatoform disorder (F45.1).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common mental disorders is somatoform disorders, with estimated prevalence rates of 5-6% in the general population [5]. A meta-analysis study showed that the prevalence rate of patients with at least one somatoform disorder according to DSM or ICD diagnosis criteria in primary healthcare facilities was 26.2%, and the prevalence rate within one year was 18.9% [6]. The highest proportion of patient diagnoses was somatoform disorder, unspecified (F45.9) at 37%, while the least diagnosed patient condition was undifferentiated somatoform disorder (F45.1).…”
Section: Introductionmentioning
confidence: 99%